Mandibular angle fractures: a comparative study between one- and two-plate fixation - Monnazzi, Marcelo Silva [UNESP]; Gabrielli, Marisa Ap Cabrini [UNESP]; Gabrielli, Mário Francisco Real [UNESP]; Trivellato, Alexandre Elias (Wiley, 2017)
Background/Aim: The mandibular angle fracture is a challenging fracture to manage. Over time, the literature has shown many types of treatment modalities and different kinds of internal fixation. The aim of this study was to evaluate the outcomes and complications of mandibular angle fractures managed by Champy's technique and two-plate fixation, over a period of 20 years. Material and methods: The files of 149 patients with 155 angle fractures fulfilled the inclusion criteria and were chosen for this study. Data were collected regarding gender, age, race, date of trauma, addictions, etiology, signs and symptoms, fracture management, and complications. Results: Prevalence was higher in males (82%), Caucasians (62%), and during the third decade of life (62%). Mean age was 26.5 years. The main cause was interpersonal violence, and the mean follow-up period was 232 days. The main signs and symptoms were pain, edema, and mouth-opening restriction. The most often associated fracture involved the mandibular condyle, and the most common complication was infection. Conclusion: There was no difference between the two modalities of treatment. However, the one-plate fixation technique had fewer complications.
Keywords: facial trauma; management; mandibular angle fracture; mandibular fracture